Top management team diversity, group process, and strategic consensus - Knight, Don; Pearce, Craig L.; Smith, Ken G.; Olian, Judy D.; Sims, Henry P.; Smith, Ken; Flood, Patrick C. (Strategic Management Journal, 1999)
This study integrated concepts from upper echelons, group process and social cognition theories to investigate how demographic diversity and group processes influence strategic consensus within the top management team (TMT), where strategic consensus is defined as the degree to which individual mental models of strategy overlap. Data from 76 high-technology firms in the United States and Ireland were used to examine three alternative models. The results showed that while demographic diversity alone did have effects on strategic consensus the overall fit of the model was not strong. Adding two intervening group process variables, interpersonal conflict and agreement-seeking, to the model greatly improved the overall relationship with strategic consensus. For the most part, TMT diversity had negative effects on strategic consensus. The model with superior fit showed both direct and indirect effects of diversity on strategic consensus. Copyright © 1999 John Wiley & Sons, Ltd.